Analysis on perceptibility and robustness of digital watermarking using discrete wavelet transform - Yusof, Yusnita; Khalifa, Othman Omran (CSEC International, 2008)
Digital watermarking is distinctive depending on the techniques used and its intended applications. This paper concentrates on invisible digital image watermarking using discrete wavelet transform. The workflow inyolyes watermark embedding, attacks and watermark extraction. Two ntethods are proposed and analyzed to imply the perceptibility and robustness, among the most important criteria of digital watermarking, using three types of attacks - JPEG compression, blurring and histogram equalization. The results are compared through subjective visual inspections and calculative measurements using PSNR for image perceptibility and SSIM Index for watermark robustness